ANALISIS PENGARUH SANKSI PAJAK DAN KUALITAS PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - N, Elly Soraya; Fakhrana, Intan (Kinerja, 2018)
Taxpayer compliance is the fulfillment of obligations undertaken by the taxationof taxpayers in order to contribute to the country's development is expected in itsfulfillment is done on a voluntary basis. The tax is very important for Indonesia becauseof the country's development of tax income for the largest contributing country.The current tax receipts for the State. One of the obstacles that can inhibit theeffectiveness of tax collection is a taxpayer compliance ( tax compliance).This study aimed to test whether the influence of Tax Sanctions against a private PersonTaxpayer Compliance and service quality Fiskus influence against a Person TaxpayerCompliance. This research using a sample on the KPP Pratama Bekasi South in the 2012-2016 sample uses probalility. The research method used is the quantitative methods withmultiple regression analysis techniques and usingthe SPSS statistical test tool version 20.0.The results of this research show that the positive effect of significant tax penalties againstprivate persons the taxpayer compliance. Quality of service significantly influential fiskusagainst taxpayer compliance people person